Perhitungan Peramalan Penjualan dalam Penyusunan Anggaran Penjualan pada PT Industri Susu Alam Murni (ISAM) - Citra Treetania Putri Rukmana; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study was conducted at PT Industri Susu Alam Murni (ISAM), which is one of the beverage industries in the city of Bandung. In preparing its sales budget, PT Industri Susu Alam Murni (ISAM) uses the average previous sales and considers market demand. The method used by the company has not been effective because there is a large difference between the sales target and actual sales where the sales target is higher than actual sales. This study aims to calculate sales forecasting using trend analysis, namely the least squares trend method and the parabolic trend method in preparing sales budgets to minimize sales budgeting errors. The type of research is descriptive research with a quantitative approach. The type of data is quantitative data, the data source is primary data and secondary data with data collection techniques through interviews and documentation. Based on the results of the study, the calculation of sales forecasting using the least squares method and the parabolic method produces a total sales forecast equal to the company's total sales realization, which is Rp. 4,562,422,500. The most appropriate sales forecasting method applied to PT Industri Susu Alam Murni (ISAM) is the parabolic method because the value of SKP obtained is the smallest compared to the method used by the company and the least squares method. The preparation of the sales budget using the quadratic method for July 2021 to June 2022 obtained a total budget of Rp. 8,875,295,327.